2013
DOI: 10.1074/jbc.m113.461202
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 Receptor-mediated Epidermal Growth Factor Receptor Transactivation through a Disintegrin and Metalloprotease Regulates Dopaminergic Neuron Development via Extracellular Signal-related Kinase Activation

Abstract: Background: Dopamine D2R-mediated ERK activation regulates dopaminergic neuronal development. Results: D2R activation induces shedding of heparin-binding EGF by activating a disintegrin and metalloproteinase (ADAM) 10 or 17, causing EGFR transactivation in mesencephalic neurons. Conclusion: D2R-mediated ERK activation regulates mesencephalic dopaminergic neuron development via EGFR transactivation through ADAM10/17. Significance: Dopaminergic system alteration through D2R-ADAM-EGFR signaling maybe associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
(37 reference statements)
1
27
0
1
Order By: Relevance
“…Previous reports suggest that DRD2 signaling leads to ERK activation [23-25, 32]. We hypothesized that this signaling may contribute to the pro-proliferative effect of DRD2.…”
Section: Resultsmentioning
confidence: 89%
“…Previous reports suggest that DRD2 signaling leads to ERK activation [23-25, 32]. We hypothesized that this signaling may contribute to the pro-proliferative effect of DRD2.…”
Section: Resultsmentioning
confidence: 89%
“…These D2-type autoreceptors represent either somatodendritic autoreceptors, known to dampen neuronal excitability (Lacey et al, 1987, 1988; Chiodo and Kapatos, 1992), or terminal autoreceptors, which mostly decrease DA synthesis and packaging (Onali et al, 1988; Pothos et al, 1998), but also inhibit impulse-dependent DA release (Cass and Zahniser, 1991; Kennedy et al, 1992; Congar et al, 2002). Therefore, the principal role of these autoreceptors is the inhibition and modulation of overall DA neurotransmission; however, it has been suggested that in the embryonic stage, the D2-type autoreceptor could have a different function in DA neuronal development (Kim et al, 2006, 2008; Yoon et al, 2011; Yoon and Baik, 2013). Thus, the cellular and molecular role of these presynaptic D2 receptors needs to be explored further.…”
Section: Dopamine Receptorsmentioning
confidence: 99%
“…D2 receptor-mediated ERK activation was found to be dependent on Gα i protein coupling, and it appears thatit requires the transactivation of receptor tyrosine kinase, which activates downstream signaling to finally activate ERK (Choi et al, 1999; Kim et al, 2004; Wang et al, 2005; Yoon et al, 2011; Yoon and Baik, 2013). Arrestin has been also suggested to contribute to D2 receptor-mediated ERK activation (Beom et al, 2004; Kim et al, 2004), which can activate MAPK signaling by mobilizing clathrin-mediated endocytosis in a β-arrestin/dynamin-dependent manner (Kim et al, 2004).…”
Section: Da-mediated Signaling In Activation Of Mitogen-activated Promentioning
confidence: 99%
“…For example, using primary dopaminergic mesencephalic cultures, we have shown that pharmacological inhibition of ERK5, and to a lesser extent ERK1 and 2, resulted in a significant loss of viability of dopaminergic neurons at day in vitro (DIV) 2, 4, 6, and 8 (Parmar et al, 2014). Moreover, others have shown that the regulation of dopaminergic neuronal development is regulated by D2 receptor‐mediated ERK activation (Kim et al, 2006; Yoon et al, 2011; Yoon and Baik, 2013). These data suggest that ERK pathways are necessary for basal survival of dopaminergic neurons during early time points and may play crucial role in the development of dopaminergic brain regions.…”
Section: Introductionmentioning
confidence: 99%